Paving Blocks Made from Plastic Waste: Environmental Solutions & Business Potential - Saepul Saepul (Institut Agama Islam Negeri Palopo, 2021)
The research in this thesis aims to find out the process of developing plastic waste products into paving blocks, to find out the business prospects of paving blocks from plastic waste in the city of Palopo and to find out the business implications of paving blocks from plastic waste in the city of Palopo. The type of research data uses research and development methods and descriptive quantitative methods. This research was conducted by conducting product-making experiments and interviews. The development techniques used by researchers are the previous research stage, the initial product development stage, the expert validation stage, and the compressive strength test stage. Analysis of the data used by the author is an analysis of the compressive strength of paving blocks, analysis of economic value, and analysis of contribution to the environment. The results showed that Sample B with a composition of 1.5 kg of plastic waste and 1.5 kg of sand, sample C with a composition of 2.25 kg of plastic waste and 0.79 kg of sand, sample D with a composition of 1.5 kg of plastic waste and 1 .9 kg meets the eligibility standard for paving block quality based on SNI 030691 1996 quality standard. Paving block products made from plastic waste have the potential to be developed into a business with a Break Event Point occurring in the 1st month. The profit by producing 1,500 paving blocks has already benefited from the business with the first month's R/C Ratio of 1.1 and the first year's R/C Ratio of 1.4. Paving block products have implications for reducing the amount of plastic waste in the city of Palopo by making plastic waste a raw material for making paving block products. 25 Kg of plastic waste and 0.79 Kg of Sand, sample D with a composition of 1.5 Kg of plastic waste and 1.9 Kg met the eligibility standards for paving block quality based on SNI 030691 1996 quality standards. Paving block products made from plastic waste have the potential to be developed into business with a Break Event Point occurring in the 1st month. The profit by producing 1,500 paving blocks has already benefited from the business with the first month's R/C Ratio of 1.1 and the first year's R/C Ratio of 1.4. Paving block products have implications for reducing the amount of plastic waste in the city of Palopo by making plastic waste a raw material for making paving block products. 25 Kg of plastic waste and 0.79 Kg of Sand, sample D with a composition of 1.5 Kg of plastic waste and 1.9 Kg met the eligibility standards for paving block quality based on SNI 030691 1996 quality standards. Paving block products made from plastic waste have the potential to be developed into business with a Break Event Point occurring in the 1st month. The profit by producing 1,500 paving blocks has already benefited from the business with the first month's R/C Ratio of 1.1 and the first year's R/C Ratio of 1.4. Paving block products have implications for reducing the amount of plastic waste in the city of Palopo by making plastic waste a raw material for making paving block products. Paving block products made from plastic waste have the potential to be developed into a business with a Break Event Point occurring in the 1st month. The profit by producing 1,500 paving blocks has already benefited from the business with the first month's R/C Ratio of 1.1 and the first year's R/C Ratio of 1.4. Paving block products have implications for reducing the amount of plastic waste in the city of Palopo by making plastic waste a raw material for making paving block products. Paving block products made from plastic waste have the potential to be developed into a business with a Break Event Point occurring in the 1st month. The profit by producing 1,500 paving blocks has already benefited from the business with the first month's R/C Ratio of 1.1 and the first year's R/C Ratio of 1.4. Paving block products have implications for reducing the amount of plastic waste in the city of Palopo by making plastic waste a raw material for making paving block products.